Quasi-adjoint third order difference equations: oscillatory and asymptotic behavior - B. Smith (International Journal of Mathematics and Mathematical Sciences)
In this paper, asymptotic properties of solutions ofΔ3Vn+Pn−1Vn+1=0          (E+)are investigated via the quasi-adjoint equationΔ3Un+PnUn+2=0.             (E−)A necessary and sufficient condition for the existence of oscillatory solutions of (E+) is given. An example showing that it is possible for (E+) to have only nonoscillatory solutions is also given.